Futuristic business studies curriculum for upper secondary schools / Chiew Wye Mei - Chiew, Wye Mei (2013)
This study is to design a Business Studies curriculum to prepare students for the future business environment. The prototype of the curriculum focused on future business needs, content, skills and values, emphasising validity and practicality. The developmental research approach, comprising ‘needs analysis’, ‘design’, and ‘evaluation’ phases, was used to build the prototype. In the needs analysis phase, users of the 1998 Business Studies curriculum were interviewed about the strengths and weaknesses of the curriculum. The findings revealed the curriculum has overlapping topics, lacked certain topics, and require officially stated skills and values. During the designing phase, interviews were conducted on various stakeholders of their perceived future business needs and their opinions of the curriculum. The Prototype I Business Studies curriculum was designed incorporating all feedback. The content and construct validity of the prototype were then approved by a panel of experts chosen randomly from the stakeholders using modified Delphi method. Prototype I was refined and developed into Prototype II. A reality check on the acceptance of Prototype II was conducted in the evaluation phase via survey on Business Studies teachers from all over Malaysia. Test of significant differences using Mann-Whitney U, Kruskal-Wallis and Chi-Square between teachers’ location of schools, as well as teaching experiences with their perceptions of importance of the Prototype II were carried out. The results did not show any significant differences on both location and teaching experiences with the teachers’ perceptions. The Futuristic Business Studies Curriculum for Upper Secondary Schools (refined Prototype II), which took into account future business needs with the appropriate content, skills and values, was perceived as ‘well designed’. A futuristic theoretical curriculum model and the developmental research approach were found suitable to develop an acceptable curriculum.